Comparative evaluation of two physically based models for the description of stress-relaxation behaviour of 9% chromium containing steel - J. Christopher; C. Praveen; B.K. Choudhary (Fracture and Structural Integrity)
An attempt has been made to evaluate the applicability of two constitutive models related to the dislocation-obstacle interactions for the description of stress-relaxation behaviour of E911 tempered martensitic steel. The first one is Feltham model (Model-I) and the Model-II proposed by Christopher and Choudhary is based on the sine hyperbolic kinetic rate formulation coupled with the evolution of internal stress. The physical constants associated with these models have been determined by the minimization of errors between experimental and predicted relaxation stress vs. hold time data for two different strain hold levels of 1.3 and 2.5% at 873 K for E911 steel. Model-II provides better prediction of stress-relaxation behaviour of the steel as compared to Model-I. In addition to prediction of relaxation stress vs. hold time data, Model-II can able to capture the evolution of internal stress, inter-barrier spacing and activation volume with the hold time. The predicted increase in inter-barrier spacing and activation volume with hold time indicated that substructural coarsening remains dominant in E911 steel under stress-relaxation conditions.